TEACHING READING COMPREHENSION OF ANALYTICAL EXPOSITION TEXT TO THE ELEVENTH GRADE STUDENTS OF SMA IN MEDAN - Sori Merianda Sigalingging; Berlin Sibarani; Sumarsih Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
This study aimed at describing how the teachers teach reading comprehension of analytical exposition text to the eleventh grade students of SMA in Medan and revealing the underlying reasons of why they do that way. This study was conducted by using descriptive qualitative research design. The subjects of this study were two English teachers who taught at the eleventh grade students of two SMA in Medan they were: SMA Negeri 4 and SMA Negeri 12 in academic year 2016/2017. The data were the recorded utterances of the teachers and the students during the teaching reading process and the transcript of the interview which were collected by observing, tape recording, and interviewing and analysed by using Miles and Huberman technique. The findings of the study showed most of the teachers’ ways did not focusing on teaching reading comprehension but rather focusing on teaching the knowledge of genre because they did not provide the use of text structure knowledge which is considered as a help to enhance comprehension. All the underlying reasons of the teachers’ ways in teaching reading comprehension of analytical exposition text did not facilitate comprehension. It was due to the misperception of the concept of teaching reading comprehension. Key words: teaching, reading comprehension, analytical exposition text